1998
DOI: 10.1111/j.1532-5415.1998.tb01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Diagnosis and Intervention in Older and Younger Patients in a Primary Care Clinic: Effect of a Screening and Diagnostic Instrument

Abstract: Decreased rates of psychiatric diagnosis and intervention in older primary care patients are of concern. Implementing the PRIME-MD will likely increase rates of diagnosis and intervention but will need to be accompanied by additional measures to eliminate age-related disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 57 publications
(77 reference statements)
0
10
0
1
Order By: Relevance
“…These studies showed that physician notification of depression status resulted in slight improvements in quality of depression care, but no replicable effects on improved depression outcomes [16]. Several later studies built on these initial failures to attempt to enhance depression outcomes by randomizing depressed primary care patients into those whose physicians were notified about a major depression diagnosis and provided with an algorithm of recommended depression care vs. those allowed to remain in usual care [17,18]. Again, no replicable effects on patient-level outcomes were demonstrated.…”
mentioning
confidence: 99%
“…These studies showed that physician notification of depression status resulted in slight improvements in quality of depression care, but no replicable effects on improved depression outcomes [16]. Several later studies built on these initial failures to attempt to enhance depression outcomes by randomizing depressed primary care patients into those whose physicians were notified about a major depression diagnosis and provided with an algorithm of recommended depression care vs. those allowed to remain in usual care [17,18]. Again, no replicable effects on patient-level outcomes were demonstrated.…”
mentioning
confidence: 99%
“…“Any depressive-anxiety-alcohol disorder” was a composite category created if women were classified as having at least one of the four psychiatric diagnoses. The PRIME-MD has been used with the elderly including those with cognitive impairment 2628. Screening instruments for bipolar disorders, thought disorders, personality disorders, or other substance abuse disorders were not used.…”
Section: Methodsmentioning
confidence: 99%
“…The paper “Psychiatric Diagnosis and Intervention in Older and Younger Patients in a Primary Care Clinic: Effect of a Screening and Diagnostic Instrument,” by Valenstein, Kales, and co‐workers, 1 reports findings in regard to the use of a standardized approach to screening for psychiatric symptoms and diagnosing mental disorders in a Veterans Administration primary care clinic. The screening instrument, the PRIME‐MD, 2 was designed specifically to probe for mood‐, anxiety‐, somatoform‐, eating‐, and alcohol‐related disorders in primary care settings.…”
mentioning
confidence: 99%
“…copies (Net Press Run), 10,450. (b) Paid and/or requested circulation; (1) Sales through dealers and carriers, street vendors and counter sales (not mailed), 541; (2) Paid or Requested mail subscriptions (include Advertisers Proof Copies/Exchange Copies), 8,509. (c) Total paid and/or requested circulation (sum of 15b(1) and 15b(2)), 9,050.…”
mentioning
confidence: 99%
See 1 more Smart Citation